Properties of arsenic sulphide (beta-As4S4) modified by mechanical activation - Balaz, Peter; Balaz, Matej; Shpotyuk, Oleh; Demchenko, Pavlo; Vlček, Miroslav; Shopska, Maya; Briancin, Jaroslav; Bujnakova, Zdenka; Shpotyuk, Yaroslav; Selepova, Barbora; Balazova, Ludmila (Springer, 2017)
Arsenic sulphide beta-As4S4 has been modified by mechanical activation in a planetary ball mill. As a consequence, the solid-state properties and dissolution yield have been influenced. The following changes were observed: the increase of specific surface area, changes in the morphology (the formation of submicron particles), the occurrence of nanoparticles (21-31 nm), changes in crystal lattice parameters and changes in the Raman shift of particular vibrations. As a consequence of these changes, the dissolution rate of beta-As4S4 has been increased, which is a challenge for the application in cancer research.
Vlastnosti sulfidu arsenitého (beta- As4S4) modifikovaného mechanickou aktivací
Keywords: in-vivo bioavailability; x-ray; physicochemical properties; realgar nanoparticles; mechanochemistry; light; as4s4; raman; diffraction; dissolution; in-vivo biologická dostupnost; x-ray; fyzikálně-chemické vlasnosti; nanočástice realgaru; mechanicky indukovaná chemie; světlo; as4s4; raman; difrakce; rozpouštění